THE PROBLEM OF INDIVIDUALIZATION OF LEARNING AS MEANS OF CREATIVE PERSONALITY BUILDING HISTORIES OF FOREIGN AND DOMESTIC PEDAGOGY (Pedagogy of Higher and Secondary Education, 2001)
The article are considered glances of foreign and domestic teachers to the problem of personalization of educating as facility of condition in forming of creative personality of teacher.